Examining the Significance and Impact of Social Entrepreneurship - Maniam, Balasundram; Engel, Jared; Subramaniam, Geetha (International Journal of Engineering and Technology, 2018)
Social entrepreneurship has garnered a significant amount of attention over the last decade or two. With so much emphasis on economic and financial return, governments and commercial businesses often neglect or provide insufficient attention towards the social and natural environments. This recent surge in non-profit and social activity from social entrepreneurs is proving to be an effective means of doing business, stirring up much controversy amongst scholars along the way. This paper dives into the hotly debated definition of social entrepreneurship and examines the types of opportunities and challenges associated with new phenomenon. Then, the report concludes with a discussion on the complexity of social entrepreneurship and why future research is needed.Â Â